Structural roofing system and method of using the same - Beccarelli, Paolo; Maffei, R. (Google Patents, 2017)
It is disclosed a structural roofing system (1) for covering an underneath area (50) comprising at least one foundation (3) to transmit the loads of said structural roofing system to the ground (4), at least one tension element (5) extending between at least two points (30, 31) of said at least one foundation (3), at least one pneumatic element (10) supported by said at least one tension element (5) with at least one portion of said pneumatic element lying on said at least one tension element (5), and at least one covering layer (2) having at least a portion located above said at least one pneumatic element (10) and supported by said at least one pneumatic element (10), wherein said at least one pneumatic element (10) keeps at distance at least part of said covering layer (2) from said at least one tension element (5), when said at least one pneumatic element is at least partially inflated. A method for the construction of roofing arrangement by the structural roofing system (1) is also disclosed.